2020
DOI: 10.1101/2020.06.26.166157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic stability and adaptation of beer brewing yeasts during serial repitching in the brewery

Abstract: AbstractAle brewing yeast are the result of admixture between diverse strains of Saccharomyces cerevisiae, resulting in a heterozygous tetraploid that has since undergone numerous genomic rearrangements. As a result, comparisons between the genomes of modern related ale brewing strains show both extensive aneuploidy and mitotic recombination that has resulted in a loss of intragenomic diversity. Similar patterns of intraspecific admixture and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…Research on fungal genome structure in response to domestication suggests large macrosyntenic rearrangements can occur frequently and rapidly within populations and can even lead to diversification of lineages 7 9 , 11 , 13 , 31 , 41 . For example, research in brewer’s yeast has shown that chromosomes can fragment and subsequently be misrepaired by being fused together at telomere regions, resulting in new chromosomes with embedded telomeric sequences within them 11 , 13 , 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on fungal genome structure in response to domestication suggests large macrosyntenic rearrangements can occur frequently and rapidly within populations and can even lead to diversification of lineages 7 9 , 11 , 13 , 31 , 41 . For example, research in brewer’s yeast has shown that chromosomes can fragment and subsequently be misrepaired by being fused together at telomere regions, resulting in new chromosomes with embedded telomeric sequences within them 11 , 13 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…This has allowed for the production of genome assemblies with high levels of contiguity, something previously difficult and expensive to attain with second generation short-read sequencing technologies. These highly contiguous genomes allow for exploration of a number of areas that were previously intractable, such as: large-scale genome structure analysis, known as macrosynteny 30 ; and longitudinal studies investigating how genome structure changes over time 31 . Large-scale genome synteny analysis is difficult to undertake with fragmented genomes, with previous efforts focused on specific loci and the ordering of the genes; this is known as microsynteny 32 35 .…”
Section: Introductionmentioning
confidence: 99%
“…SMARTdenovo has been available since 2015 on github, but its performance not only remains comparable with current assemblers, and but also has several advantages as described. Furthermore, given its excellent performance for use on corrected long sequence reads, it continues to be widely used in for genome assembly projects today [33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given its excellent performance for use on corrected long sequence reads, it continues to be widely used in for genome assembly projects today [34][35][36][37][38][39][40][41][42][43].…”
Section: Assembling the Genome Of The Wild Tomatomentioning
confidence: 99%